Nature, Man and God in Medieval Islam : Volume Two - Calverley, Edwin Elliott,; Pollock, James W., (Middle East and Islamic Studies - Book Archive 2000-2006., 2002)
A contemporary to Thomas Aquinas in Latin Catholic Italy, and with a parallel motivation to stabilize each his own civilization in its flux and storm, 'Abd Allah Baydawi of Ilkhan Persia wrote a compact and memorable Arabic Summation of Islamic Natural and Traditional Theology. With the same strokes of his pen he presented the Islamic version of the Science of Theological Statement, bafflingly called "Kalam" while familiarly embracing "Theology". Baydawi's Tawali'al-Anwar min Matal'al-Anzar (Rays of Dawnlight Outstreaming from Far Horizons of Logical Reasoning), with Mahmud Isfahani's commentary, is a formidably clear logical and mental vision of mankind's final completion as a spiritual structure in Islam. Reality - in nature's Possible mode, in an apodictic Divine mode, and in humanity's heroic Prophetic mode - comprises man's Worldview and is the Theme of the Baydawi/Isfahani discourse. The Edifice of Man and Humanity's evanescent Evidence within it are both hugely arresting and moving. The print edition is available as a set of two volumes (9789004121027).